2020
DOI: 10.1371/journal.pone.0236470
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the fecal microbiota of patients with spinal cord injury

Abstract: Objectives Spinal cord injury (SCI) is associated with severe autonomic dysfunction. Patients with SCI often suffer from a lack of central nervous system control over the gastrointestinal system. Therefore, we hypothesized that patients with SCI would cause intestinal flora imbalance. We investigated alterations in the fecal microbiome in a group of patients with SCI. Methods Microbial communities in the feces of 23 patients and 23 healthy controls were investigated using high-throughput Illumina Miseq sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…In a Chinese cohort study, Zhang et al observed an increase in Proteobacteria and Verrucomicrobia and reduced Bacteroidaceae and Bacteroides in patients with chronic traumatic complete SCI (109). Lin et al also analyzed 46 Chinese subjects (23 SCI patients vs. 23 healthy controls) and reported that the abundances of Parabacteroides, Alistipes, Phascolarctobacterium, Christensenella, Barnesiella, Holdemania, Eggerthella, Intestinimonas, Gordonibacter, Bilophila, Flavonifractor, and Coprobacillus were higher in the patients with SCI than those in the health individuals (110). Another clinical study with 54 Turkish participants (41 SCI patients vs. 13 healthy controls) identified that butyrateproducing microbes of the Firmicutes phylum are significantly reduced in SCI patients than healthy controls (108).…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…In a Chinese cohort study, Zhang et al observed an increase in Proteobacteria and Verrucomicrobia and reduced Bacteroidaceae and Bacteroides in patients with chronic traumatic complete SCI (109). Lin et al also analyzed 46 Chinese subjects (23 SCI patients vs. 23 healthy controls) and reported that the abundances of Parabacteroides, Alistipes, Phascolarctobacterium, Christensenella, Barnesiella, Holdemania, Eggerthella, Intestinimonas, Gordonibacter, Bilophila, Flavonifractor, and Coprobacillus were higher in the patients with SCI than those in the health individuals (110). Another clinical study with 54 Turkish participants (41 SCI patients vs. 13 healthy controls) identified that butyrateproducing microbes of the Firmicutes phylum are significantly reduced in SCI patients than healthy controls (108).…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…Since these groundbreaking studies, there has been an explosion of interest in how gut microbiota are altered after SCI, and how modulation of the gut microbiome might improve both neurological and immunological outcomes for SCI individuals [ 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ]. In regard to peripheral immunity, a recent study demonstrated that after a T9 contusive injury in mice, the gut microbiome displayed a reduced Firmicutes to Bacteroidetes phyla ratio as well as an increase in the phylum Proteobacteria that contains Gram-negative bacteria that produce the endotoxin LPS, which is associated with systemic inflammation [ 157 ].…”
Section: Potential Interventions To Improve Immunological Function Post-scimentioning
confidence: 99%
“…We found that the most dominant phyla in the gut of Yucatan minipigs, making up almost 98% of all species detected, include Bacteroidetes, Firmicutes, Spirochaetes, Tenericutes, Proteobacteria and Actinobacteria. At this level of classification (phylum), the fraction of each bacterial phyla present in the gut largely resembles humans and other mammalian [18,[27][28][29][30][31][32][33], as well as murine intestinal bacteria [12,28]. However, although some of the gut microbes present in murine species are shared with the human and pig microbiome, Ley et al (2005) demonstrated that almost 85% of the subgenera present in the mouse gut are not present in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Those performed in murine models examine the acute and subacute phases of injury and generally occur < 4-8 weeks post-SCI [42,49,66]. In contrast, human studies have to date been largely confined to more chronic SCI patients [33,40,41] although we are aware of efforts to characterize the microbiome in acutely injured patients. In order to address this issue, studies need to be conducted longitudinally in acute SCI patients within the first week of their injury with prospective assessment of functional outcomes with microbial composition to correlate specific bacterial groups with outcome measures such as sensorimotor recovery, or neuropathic pain.…”
Section: Bacterial Fluctuation As Time-dependent Phenomenonmentioning
confidence: 99%